2020
DOI: 10.1186/s12872-020-01456-7
|View full text |Cite
|
Sign up to set email alerts
|

Circulating heat shock protein 27 as a novel marker of subclinical atherosclerosis in type 2 diabetes: a cross-sectional community-based study

Abstract: Background: Heat shock protein 27 (HSP27) has been proposed as a vital protective factor in atherosclerosis. The objective of the present study was to evaluate the association between circulating HSP27 and carotid intima-media thickness (IMT) in individuals with type 2 diabetes and to determine whether HSP27 represents an independent marker of subclinical atherosclerosis in this patient population. Methods: We performed a cross-sectional community-based study in 186 Chinese subjects with a median duration of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…16 Recent studies have reported several potential serum markers for screening of diabetic vascular complications, such as serum fibroblast growth factor 23, 17 serum sclerostin, 18 and circulating Hsp27. 19 In addition, heat shock proteins (HSPs) can be transported to the plasma membrane and released extracellularly, resulting in detectable levels of HSP in the blood. This finding has prompted clinical studies exploring the potential use of HSP and anti-HSP antibodies as serum biomarkers for DM complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Recent studies have reported several potential serum markers for screening of diabetic vascular complications, such as serum fibroblast growth factor 23, 17 serum sclerostin, 18 and circulating Hsp27. 19 In addition, heat shock proteins (HSPs) can be transported to the plasma membrane and released extracellularly, resulting in detectable levels of HSP in the blood. This finding has prompted clinical studies exploring the potential use of HSP and anti-HSP antibodies as serum biomarkers for DM complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, fewer than 10% of patients have typical clinical symptoms and the lack of effective treatments affects patients’ prognoses 16. Recent studies have reported several potential serum markers for screening of diabetic vascular complications, such as serum fibroblast growth factor 23,17 serum sclerostin,18 and circulating Hsp27 19. In addition, heat shock proteins (HSPs) can be transported to the plasma membrane and released extracellularly, resulting in detectable levels of HSP in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Recent studies have reported several potential serum markers for the screening of diabetic vascular complications, such as CD36, YKL-40, [17] hepatocyte growth factor, [18] serum broblast growth factor 23, [19] serum sclerostin, [20] serum growth differentiation factor 15, [21] and circulating Hsp27. [22] In addition, heat shock proteins (HSPs) can be transported to the plasma membrane and released extracellularly, resulting in detectable levels of HSPs in the blood. This nding has prompted clinical studies exploring the potential use of HSPs and anti-HSP antibodies as serum biomarkers for DM complications.…”
Section: Discussionmentioning
confidence: 99%
“…In the retina, HSP27 may play a role as an endothelial barrier in conjunction with a general anti-apoptotic protein since downregulation of HSP27 in retinal capillary endothelial cells may lead to a vulnerable environment and increase apoptosis [ 26 ]. Elsewhere, HSP27 has been proposed as a vital protective factor in atherosclerosis [ 27 ]. Given that vascular dysregulation is a possible systemic risk factor for glaucoma, this may be an important finding by which to limit development or progression of glaucoma [ 28 ].…”
Section: Discussionmentioning
confidence: 99%